Recognising developmental coordination disorder in Foundation Phase classrooms - Nicola L. Winson; Jean V. Fourie (South African Journal of Childhood Education, 2020)
Background: Developmental coordination disorder (DCD) is a neurodevelopmental motor disorder affecting 5% to 6% of children globally. The motor skills deficit associated with DCD is characterised by its impact on academic productivity, activities of daily living and play. Although the Department of Education’s (2014) policy on screening, identification, assessment and support (SIAS) calls for teachers to be the first line of identification of learning barriers, teachers are often unaware of the characteristics of DCD and have difficulty in recognising the condition.